Assessment and outlook of variable retort temperature profiles for the thermal processing of packaged foods: Plant productivity, product quality, and energy consumption. (June 2020) - Simpson, Ricardo; Jiménez, Diego; Almonacid, Sergio; Nuñez, Helena; Pinto, Marlene; Ramírez, Cristian; Vega-Castro, Oscar; Fuentes, Lida; Angulo, Alejandro
Abstract: Thermal processing has been used for packaged foods for many years and remains one of the most common and safe processes to preserve foods and extend their shelf life. Advances in thermal processing in the last two decades have helped maintain its relevance in international food trades. In this study, we aimed to gain a better understanding of thermal food processing using variable retort temperature profiles (VRTPs). VRTPs were assessed to optimize processes, either by ensuring high quality level or minimizing the operating process time. Based on the research results, VRTPs could improve quality retention; however, the improvement was not sufficient to be detectable by consumers and to justify implementation of VRTPs at the industrial level. Our general assessment provided a preliminary guide for processors to discover real opportunities for VRTPs, e.g., increased productivity by reducing operating process time and energy consumption. Highlights: Thermal processing is still one of the most common and safe processes for foods. Variable retort temperature profiles (VRTPs) significantly reduce processing time. VRTPs improve product quality, but not detectable enough by the consumers. VRTPs are advantageous in significantly increase the productivity of the plant. VRTPs increase plant productivity and simultaneously reduce energy consumption.